Islamic Bioethics and Secular Bioethics and Interaction between them: Interaction between Islamic Bioethics and Secular Bioethics - Abbasi , Mahmoud; Shamsi Gooshki, Ehsan (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: Nowadays, we are observing the increasing development of sciences, particularly biological sciences and medicine. In the Muslim world, the ethical requirements of such scientific developments are taken into account without paying sufficient attention to their indigenous and Islamic aspects. Even international institutions are not properly informed of the need for the religious aspects of bioethical discourse in Muslim countries. Hence, this study attempts to address the differences in the ideologies of these two ethical theories. Materials and Methods: In this review article, the keywords "bioethics", "Islam", "secularism", "philosophy of ethics", "ideology differences" and "ethical theories in secularism" were searched in PubMed, SID, and Google Scholar databases and the relevant literature was determined and analyzed. Ethical Considerations: Honesty and integrity were taken into consideration in searching, analyzing, and reporting the texts. Findings: Of the appropriate methods in analyzing the texts, one is the comparative study between the ideological and meta-ethical foundations of Islamic bioethics and secular bioethics, some of which are: the differences in the belief in the origin of existence and the Creator of existence; differences in the attitudes towards the totality of existence; differences in the views of the materialistic existence and the laws governing it. In addition, there exist anthropological differences in these two ethical theories, among which we can refer to the differences in the attitudes towards the creation of human beings, the differences in the attitudes towards the dimensions of human existence, and life after death. Finally, we can also refer to the meta-ethical differences between Islamic bioethics and secular bioethics, including the difference in moral ontology, the difference in ethical epistemology, ethical semantics, as well as several similarities between Islamic bioethics and secular bioethics that are mostly normative. Conclusion: Accepting the differences and similarities can be found as a present reality to begin a constructive bilateral dialogue and to introduce the fundamentals of Islamic bioethics. *Corresponding Author: Mahmoud Abbasi; Email: dr.abbasi@sbmu.ac.ir; ORCID: https://orcid.org/0000-0002-4223-6818 Please cite this article as: Abbasi M, Shamsi Gooshki E. Islamic Bioethics and Secular Bioethics and Interaction between them. Bioeth Health Law J. 2021; 1:1-10: (e3). http://doi.org/10.22037/bhl.v1i1.38127